Evolution of Moving Images in Documentary Film-Making: a study from the Middle-Eastern perspective - Rana, Madiha Faiz; Anamalai, Subhashini; Othman, Azliza (2018)
This paper is focused on the evolution of moving images in documentaries whereas the study is conducted on the perspective of Middle East. The core aims and title of the study is “to find out the evolution of moving images in documentary film-making: a study from the Middle-Eastern perspective”. While the objectives which are assigned to this study are to determine the way in which the animation is used in the documentaries to increase the impacts as well as the other objective is to explore the cultural and socio-political impacts of incorporating animations in documentary film- making in the contemporary scenario in the Middle-East. For the conduction of research Observational research method is used which contained hermeneutic or interpretivist research model. Participant observation and unstructured interview are used to collect the data.